2014
DOI: 10.4271/2014-01-2822
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling and Experimental Characterization of a Pressure-Assisted Multi-Stream Injector for SCR Exhaust Gas After-Treatment

Abstract: Simulations for a pressure-assisted multi-stream injector designed for urea-dosing in a selective catalytic reduction (SCR) exhaust gas system have been carried out and compared to measurements taken in an optically accessible high-idelity low test rig. The experimental data comprises four different combinations of mass low rate and temperature for the gas stream with unchanged injection parameters for the spray. First, a parametric study is carried out to determine the importance of various spray sub-models, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…A constant injection velocity of 27.4 m/s was prescribed which was determined from the experiment. For secondary atomization, the model of KH-RT [28] has been activated, despite conclusions reached in [20] where it is reported that due to low Weber numbers secondary break-up is unlikely to occur. Based on the parametric study reported in [20], 'buoyancy' has been activated and the 'Bai' spray-wall interaction model, 'advanced' droplet collision model and film models are also applied in this work…”
Section: Numerical Setupmentioning
confidence: 85%
See 3 more Smart Citations
“…A constant injection velocity of 27.4 m/s was prescribed which was determined from the experiment. For secondary atomization, the model of KH-RT [28] has been activated, despite conclusions reached in [20] where it is reported that due to low Weber numbers secondary break-up is unlikely to occur. Based on the parametric study reported in [20], 'buoyancy' has been activated and the 'Bai' spray-wall interaction model, 'advanced' droplet collision model and film models are also applied in this work…”
Section: Numerical Setupmentioning
confidence: 85%
“…Planar Mie scattering and PIV [29] as well as CFD simulations [20] have shown numerous effects of interest occurring off-center. To describe the spray transversal structure, the droplet size distribution analyzes all droplet data along the y-direction at given x-and z-coordinates.…”
Section: Off-center Distributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A UWS spray wall interaction also cannot be avoided in most SCR applications due to insufficient entrainment, slow evaporation and thermolysis, and the inertia of the droplets. It causes local cooling of the wall and a wall film will form if the wall temperature decreases below a critical temperature (Birkhold et al, 2006;Varna et al, 2014;Spiteri et al, 2015). Kuhnke et al (2004) and Abu-Ramadan et al (2012) divided the UWS spray impingement into four regimes based on the properties and energy of the droplet, and the wall surface condition.…”
Section: Introductionmentioning
confidence: 99%